Changes on the initial conceptions and induction on the nature of mathematics and its didactics of an undergraduate students program in mathematics and statistics (2014)
This paper shows some results of a study whose objective was to investigate the conceptions that students have about a basic training program for teachers of mathematics, about the nature of mathematics, and the way they learn and teach. The theoretical framework of the project is described in general terms as well as the analytical categories established for the design and validation of an instrument that identified the conceptions of students of the Licenciatura of Mathematics and Statistics, at Pedagogical and Technological University of Colombia, Duitama Branch. Some statistics techniques used to analyze the collected information are highlighted, concluding that freshmen retain a static view of how to teach and assess maths, while the students from the last semesters have modified their conceptions, considering mathematics as a human and social construction in constant dynamism, although with slight overtones of rigidity in their evaluation.